(untitled) (Annals of Medical Research, 2023)
Aim: While type 2 diabetes (T2DM) is increasing rapidly, developing diabetic complications are the leading cause of morbidity and mortality. Biochemical markers are important for early diagnosis and treatment of nephropathy, which is a common complication. The aim of this study is to evaluate serum ischemia-modified albumin (IMA) levels in the development of diabetic nephropathy in T2DM patients and to determine the effectiveness of this parameter in predicting the presence and severity of nephropathy. Materials and Methods: 68 adult patients diagnosed with T2DM and 30 healthy controls were included in this study. The T2DM group consisted of 34 patients without microalbuminuria (<30 mg/g) and 34 patients with microalbuminuria (30–300 mg/g) according to albumin/creatinine ratio (UACR). Biochemical data and serum IMA levels of the patient and control groups were measured and compared. Results: In terms of IMA levels, the difference between T2DM patients with microalbuminuria (0.55 ± 0.08 ABSU) and without microalbuminuria (0.42 ± 0.05 ABSU) and control (0.37 ± 0.08 ABSU) groups was significant (p<0.0001). The T2DM group with microalbuminuria had the highest glucose, HbA1c, UACR, and IMA levels. There was a positive correlation between IMA levels and UACR (r = 0.541, p < 0.001). IMA had a weak correlation with HbA1c (r = 0.345, p = 0.002). ROC analysis was performed and the IMA test had a high diagnostic value in the diagnostic differentiation of T2DM patients with microalbuminuria. According to multiple logistic regression analysis, IMA levels were an independent risk factor for DN (p = 0.003). Conclusion: Our data showed that IMA values increased significantly in diabetic patients, especially in those with microalbuminuria, and this increase was correlated with UACR levels. This study has shown that increased IMA levels are an important marker for the presence and severity of microalbuminuria in diabetic patients and therefore may be important in the early detection of renal dysfunction in T2DM. We even think that it can be used as an important marker in the follow-up of diabetic patients, even before the development of microalbuminuria.